Essays on real exchange rate volatility and openness in international trade - Salazar Neaves, Abelardo (2010)
This work comprises five chapters that explore in detail issues related to real exchange rate volatility and trade openness. In the case of real exchange rate volatility, we start with the decomposition of this measure to determine the relative contribution of traded and nontraded goods to the variance of the real exchange rate. We obtain evidence in favour of a relevant role for non-traded goods.